(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2019)
As technology has advanced, faculty members have many ways to connect with current and prospective students. Yet, no extant research has examined online faculty profiles on institutional (.edu) websites. To inform graduate student choice literature, we examined a random sample of 1,500 online faculty profiles across 500 U.S. graduate programs. Findings suggest assistant and associate professors publish the most informative online profiles, whereas private for-profit professors and lecturers publish the least informative profiles. In addition, zero faculty members self-identified their pronouns, race and ethnicity, or their first-generation college student status in their biographical statement. Implications for research and practice in U.S. and international contexts are addressed.